Development of NIR photocleavable nanoparticles with BDNF for vestibular neuron regeneration - Celine DG. Abueva; Sung Ryeong Yoon; Nathaniel T. Carpena; Seung Cheol Ahn; So-Young Chang; Ji Eun Choi; Min Young Lee; Jae Yun Jung (Journal of Nanobiotechnology)
Abstract Among nanoparticle platforms, light or photoresponsive nanoparticles have emerged as a promising drug delivery strategy with spatiotemporal control while minimizing off-target effects. The characteristic absorption spectrum of the photoresponsive moiety dictates the wavelength of light needed to activate bond cleavage. However, the low tissue penetration depth limit and short-wavelength ultraviolet (UV) cellular toxicity are considered disadvantageous. This study developed a vestibular ganglion neuron organoid as a model for vestibulopathy. UV and near-infrared (NIR) radiation targeted the inner ear and neural cells, followed by toxicity evaluation. A significantly smaller toxicity of NIR light was confirmed. The photocleavage release of brain-derived neurotrophic factor (BDNF) was used by applying NIR wavelength. The results indicate that polyethylene glycol octamethylene diamine derivative conjugated with leucomethylene blue with an ethanolamine linker nanoparticle can be effectively disassembled and release BDNF when using the 808 nm laser as a trigger. The findings of the cytotoxicity assay suggest that photocleavable nanoparticles (PCNs) and laser irradiation are safe and biocompatible for human-derived and neural progenitor types of cells. Phototriggered BDNF release by NIR laser supported the growth and differentiation of human neural progenitor cells in culture. In addition, the vestibulopathy organoid exhibited a significant regenerative effect. This study harnesses the full potential of NIR laser PCNs to treat vestibular neuropathies. Graphical abstract